Audrey R. Kahin y George McT. Kahin. Subversion as Foreign Policy. The Secret Eisenhower and Dulles Debacle in Indonesia. Seattle & Londres: University of Washington Press, 1995. 318 pp. - Anguiano Roch, Eugenio (Estudios de Asia y África, 1998)
-